Genetic improvement of chickpea through MAS for abiotic stresses - Kundu, Antim; Sanwal, S. K.; Kumar, Ashwani; Singh, Vikram; Nain, Ashish (Journal of Soil Salinity and Water Quality, 2023)
Chickpea, is vital pulse crop under rain-fed conditions and is important source of protein, fibre and healthy fats befitting people globally. But the crop’s productivity is hindered by various abiotic stressors like heat, drought, cold, and salinity. To address these challenges, multiple biochemical, physiological, and molecular mechanisms have been explored and multiple genes contributing to enhance abiotic stress tolerance has been identified. Advanced molecular biology tools and techniques like transcriptomics, proteomics, and metabolomics have enabled development of molecular markers which are important for gene/allele introgression. These markers facilitate marker-assisted selection (MAS) for yield components vis-à-vis abiotic stress tolerance and thus make the genetic improvement in chickpea faster. Promising outcomes have emerged from studies involving transgenic chickpea plants and gene editing techniques to develop drought-tolerant chickpea varieties. The present review focusses on use of marker assisted breeding and marker assisted selection to obtain chickpea genotypes tolerant to abiotic stress, especially in the context of climate change. Finally, we propose further research and steps to take in the era of advanced molecular biology techniques.